2016
DOI: 10.1299/mej.16-00269
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on solution and diffusion process of single carbon dioxide bubble in seawater

Abstract: Solution and diffusion process of carbon dioxide (CO 2 ) in seawater is important in the research and development of CO 2 ocean sequestration technology to mitigate global warming. In this study, solution and diffusion process of single CO 2 bubble in seawater and pure water were experimentally studied under various pressures and temperatures to evaluate the transport process of CO 2 in seawater. The solution process was conducted in a test vessel. CO 2 bubble was generated by a CO 2 bubble generator installed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…This result contrasts those from previous studies, which show that the CO 2 diffusion coefficient is greater in distilled water than in sea water. Table 5 shows that the diffusivity and Schmidt number are different based on solvent type [9,17]. As seen in Equation 4, the mass transfer coefficient is affected by diffusivity and Schmidt number; however, the effect of the Schmidt number is greater than that of diffusivity.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result contrasts those from previous studies, which show that the CO 2 diffusion coefficient is greater in distilled water than in sea water. Table 5 shows that the diffusivity and Schmidt number are different based on solvent type [9,17]. As seen in Equation 4, the mass transfer coefficient is affected by diffusivity and Schmidt number; however, the effect of the Schmidt number is greater than that of diffusivity.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Liu et al [9] experimented on the dissolution and diffusion process of a single CO 2 bubble in sea water and pure water and found that the extinction speed of a bubble is faster if the pressure is higher, the solvent is pure water, and the initial bubble diameter is smaller. Carderbank et al [8] derived the rate of solution, shape, and mass transfer coefficient of CO 2 bubbles in distilled water through experiments.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…where 𝐷 is the diffusion coefficient of CO2 in the seawater, 1.6  10 -9 m 2 /s [54,55]. Therefore, the length scale for the diffusion of the rising CO2 drops is:…”
Section: Deep Ocean Injectionmentioning
confidence: 99%